Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.31234/osf.io/c3qkm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mental representation of non-numerical quantifiers: The Spatial-Linguistic Association of Response Codes (SLARC) effect.

Abstract: How quantifiers are represented in the human mind is still a topic of intense debate. Seminal studies have addressed the issue of how a subclass of quantifiers, i.e. number words, is spatially coded displaying the SNARC (Spatial-numerical Association of Response Codes) effect; yet, none of these studies have explored the spatial representation of non-numerical quantifiers such as “some” or “many”. The aim of the present study is to investigate whether non-numerical quantifiers are spatially coded in the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Very recent behavioral studies for instance have reported SNARC-like effects on the processing of quantifiers, with left-hand responses being faster in small-quantity quantifiers (e.g., “few”) than with large-quantity quantifiers (“many,” cf. Abbondanza et al, 2021). Clinical studies also report intact comprehension of number words and quantifiers after temporal lobe damage (Butterworth et al, 2001; Cappelletti et al, 2006), whereas damage to the parietal cortex yields impairments in numerical cognition, magnitude judgments, and quantifier comprehension while preserving object understanding (Halpern et al, 2004; Morgan et al, 2011).…”
Section: Evidence For Emergencementioning
confidence: 99%
“…Very recent behavioral studies for instance have reported SNARC-like effects on the processing of quantifiers, with left-hand responses being faster in small-quantity quantifiers (e.g., “few”) than with large-quantity quantifiers (“many,” cf. Abbondanza et al, 2021). Clinical studies also report intact comprehension of number words and quantifiers after temporal lobe damage (Butterworth et al, 2001; Cappelletti et al, 2006), whereas damage to the parietal cortex yields impairments in numerical cognition, magnitude judgments, and quantifier comprehension while preserving object understanding (Halpern et al, 2004; Morgan et al, 2011).…”
Section: Evidence For Emergencementioning
confidence: 99%